Modern Approach To Organization Of Psychological Services In The Education System (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article discusses the reforms in the education system, the work carried out through them, the types of psychological services, as well as the goals and objectives. The development of school education, which is considered the first stage of education in the Republic of Uzbekistan, has been one of the priority tasks of state policy. At the same time, large-scale reforms are being implemented in our country aimed at radically improving the school education system, establishing various forms of preschool educational organizations, providing them with highly qualified, modern-minded educators and specialists, improving the quality of school education, and introducing advanced foreign experiences into the educational process